Prophylactic anticoagulant therapy is associated with improved survival in ICU patients with non-COVID-19 pneumonia: a retrospective cohort study - Hu, Haiming; Zhu, Yixing; Hu, Ruikang; Zhao, Lijuan; Zeng, Xiangwen; Wu, Xue; Qiu, Rui; Nie, Yihao; Sharma, Lokesh; Chang, De (Frontiers in Pharmacology, 2025)
BackgroundCoagulation disorders are common complications in patients with pulmonary infections. Studies have suggested beneficial effects of anticoagulant therapies in patients with COVID-19. However, the usefulness of prophylactic anticoagulant therapies in patients with non-COVID-19 pulmonary infections is still a matter of debate. This study aimed to assessed the impact of prophylactic anticoagulant therapy in ICU patients with non-COVID-19 pneumonia.MethodsPatients were identified from the Medical Information Mart for Intensive Care-IV database. Propensity score matching (PSM) was utilized to minimize differences. Kaplan-Meier survival analysis was performed to assess mortality. Univariate and multivariate Cox regression models were used to identify prognostic factors for short-term mortality (7-day). The E-value was calculated to unmeasured confounding. To further explore the optimal anticoagulant administration, subgroup analyses were performed. We also explored the optimal administration strategies including the timing and duration of anticoagulant therapy.ResultsA total of 1,000 ICU patients were included, with 500 receiving prophylactic anticoagulation therapy and 500 not. Both 7-day mortality (7.6% vs. 19.6%; p < 0.001) and 30-day mortality (19.6% vs. 31.2%; p < 0.001) in the anticoagulant group were lower than non-users. Kaplan-Meier survival analysis also showed a significantly lower prevalence of short-term mortality in patients who used anticoagulants. Both univariate (HR, 0.36; 95% CI, 0.25-0.53; p < 0.001) and multivariate (HR, 0.30; 95% CI, 0.21-0.44; p < 0.001) Cox regression analyses consistently demonstrated a significant reduction in short-term mortality associated with anticoagulation therapy. Subgroup analysis revealed that anticoagulant therapy was associated with reduced short-term mortality across most subgroups. Further analysis showed that late (≥6 h) and non-short-term (≥7 days) anticoagulation therapy were more effective.ConclusionOur results support the potential value of prophylactic anticoagulation therapy as a strategy to improve survival in ICU patients with non-COVID-19 pneumonia.